Cleaner synthesis of preclinically validated vaccine adjuvants - Romerio, Alessio; Peri, Francesco (Frontiers in Chemistry, 2023)
We developed synthetic glycophospholipids based on a glucosamine core (FP compounds) with potent and selective activity in stimulating Toll-Like Receptor 4 (TLR4) as agonists. These compounds have activity and toxicity profiles similar to the clinically approved adjuvant monophosphoryl lipid A (MPLA), included in several vaccine formulations, and are now in preclinical phase of development as vaccine adjuvants in collaboration with Croda International PLC. FP compounds synthesis is shorter and less expensive than MPLA preparation but presents challenges due to the use of toxic solvents and hazardous intermediates. In this communication we describe the optimization of FP compounds synthesis. The use of regio-and chemoselective reactions allowed to reduce the synthesis steps, improve process scalability, overall yield, safety and Process Mass Intensity (PMI), thus paving the way to the industrial scale-up of the process.